MOTORCYCLE SPARE PARTS MANAGEMENT USING THE EOQ METHOD - Suhardi, Agatha Rinta (Universitas Prof. Dr. Moestopo (Beragama), 2025)
In the 1960-1970s, Indonesia was in a period of massive development, to support this development, several important factors were needed, namely transportation, and immediately the Indonesian people really wanted to have a practical and economical two-wheeled motorcycle. The high demand for two-wheeled motorcycles created many new technologies attached to every motorcycle in Indonesia. The specifications of two-wheeled motorcycles sold on the market also vary from 100cc-200cc, and have different motorcycle models from underbones, automatic underbone motorcycles, injection automatic scooters and sport bikes. The number of two-wheeled motorcycle enthusiasts in the country, gives its own meaning and trend to two-wheeled motorcycle manufacturers, no longer only used by men but women also now use motorcycles in supporting their daily activities. Inventory management is the process of planning, controlling, and supervising the stock of goods or materials owned by an organization that aims to ensure the availability of the right goods or materials, in the right quantity, in the right place, and at the right time, with efficient costs. This study aims to analyze the inventory data of consumable motorcycle spare parts which are supporting products for motorcycle repair activities at PT. Y. The research method used is descriptive analysis using the economic quantity ordering method (EOQ). The results of this study indicate that PT. Y has the most economical number of orders of 6,324 units, with orders that must be made 48 times per year, and the company places orders once every 8 days in one year. With a total cost of Rp 9,486,833.02.